Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Anggota Satuan Intelkam Kriminal Kepolisian Polsek Ampenan - Nova Putro Sadprawi (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
This research aims to determine the influence of motivation and work environment on the performance of police officers at the Ampenan Police. There are several problems behind this research, ranging from members' performance not being optimal to an inadequate work environment. There are three variables in this research, namely, two independent variables and one dependent variable. The independent variables are motivation (X1) and work environment (X2) and the dependent variable is performance (Y). The population of this study was members of the Ampenan Police, totaling 60 people, while the research sample was 52 people. The method used in this research is a quantitative method, with primary data collected using a questionnaire, consisting of 26 statements distributed to the entire sample. The regression model used is multiple linear regression analysis, T Test, F Test. The results of the research show that the Motivation Variable (X1) has an effect, but the effect is not significant on performance at the Ampenan Police, which is indicated by a significance value greater than 0.05. The Work Environment variable (X2) partially influences performance as evidenced by the t test value where the significant value of the Work Environment variable (X2) is smaller than 0.05, namely 0.000. The results of simultaneous hypothesis testing, the independent variables consisting of Motivation (X1) and Work Environment (X2) simultaneously have a significant influence on Performance (Y) at the Ampenan Police, with a significant value of 0.000, which is smaller than 0.05. The work environment variable has the most dominant influence on the performance of Intelkam unit members at Ampenan Police, which is acceptable, this is shown by the Work Environment (X2) having the largest β (beta) coefficient value, namely 0.501 if we compare it with the Motivation variable (X1) which has a β coefficient (beta) 0.068.